The Role of Energy Balance in Successful Aging Among Elderly Individuals: The Multinational MEDIS Study. (December 2015) - Tyrovolas, Stefanos; Haro, Josep Maria; Mariolis, Anargiros; Piscopo, Suzanne; Valacchi, Giuseppe; Makri, Kornilia; Zeimbekis, Akis; Tyrovola, Dimitra; Bountziouka, Vassiliki; Gotsis, Efthimios; Metallinos, George; Tur, Josep-Antoni; et al.
Objective: The determinants that promote living beyond life expectancy and successful aging still remain unknown. The aim of the present work was to evaluate the role of energy balance in successful aging, in a random sample of older adults living in the Mediterranean basin.Method: During 2005 to 2011, 2, 663 older (aged 65-100 years) adults from 21 Mediterranean islands and the rural Mani region (Peloponnesus) of Greece were voluntarily enrolled in the study. Dietary habits, energy intake, expenditure, and energy balance were derived throughout standard procedures. A successful aging index (range = 0-10) was used.Results: After adjusting for several confounders, high energy intake (i.e., >1, 700 kcal/day), b-coefficient [95% CI] = −0.21[−0.37, −0.05], as well as positive energy balance, b-coefficient [95% CI] = −0.21 [−0.37, −0.05], were inversely associated with successful aging.Conclusion: A diet with excessive energy intake and a positive energy balance seems to be associated with lower quality of life, as measured through successful aging.